Robert's rules of order, newly revised - Robert, Henry M.; Robert, Sarah Corbin (Reading, Mass. Addison-Wesley, 1990)
A work on parliamentary procedure.
Introduction; Principles Underlying Parliamentary Law; The Deliberative Assembly: Its Types and Their Rules; The Conduct of Business in a Deliberative Assembly; Descriptions of Motions in All Classifications; Meeting and Session; The Main Motion; Subsidiary Motions; Privileged Motions; Incidental Motions; Motions that Bring a Question Again Before the Assembly; Renewal of Motions; Dilatory and Improper Motions; Quorum; Order of Business and Related Concepts; Assignment of the Floor; Debate; Voting; Nominations and Elections; Officers; Minutes and Officers Reports; Boards and Committees; Mass Meetings; Organization of a Permanent Society; Bylaws; Conventions; Disciplinary Procedures.
Includes index.
95233
Keywords: Parliamentary practice